CHARTERING GAWAD KALINGA COMMUNITIES: A CASE OF DEVELOPMENT IN EASTERN SAMAR, PHILIPPINES - Odivilas, Hilarion A.; Odivilas, Florita O. (European Scientific Journal, ESJ, 2015)
The study evaluated the implementation of GK program components in the communities in Eastern Samar. A descriptive method was employed utilizing a questionnaire to identify the profile of the implementers, the program implementation and the difference of perceptions of the beneficiaries and implementers of the GK program. The results showed that 35.7% of the implementers were 51-60 years old, 64.3% were males, 35.7% finished bachelor’s degree and 28.6% attended 4-6 and 1-3 trainings respectively. It was revealed that shelter and environment and values components were evaluated to be adequate while the rest of the program components were inadequate. The difference of perception of the two-group of respondents on the implementation of the program yielded no significant difference.